ANALISIS PERBANDINGAN KINERJA INDUSTRI PERBANKAN INDONESIA SEBELUM DAN SESUDAH ERA INOVASI DAN TEKNOLOGI - Andriyanti, Rissa Oktaviana; Fatimah, Atika (Politeknik Negeri Lhokseumawe, 2024)
Abstract: Before innovation and technology were applied to the banking industry, banking operations were not fully integrated and business insight in decision making was still limited due to limited data. This data limitation is caused by banks which still tend to rely on periodic financial reports and manual analysis. However, after the era of innovation and technology marked by big data, sophisticated cloud system and artificial intelligence (AI), it is hope that the banking industry can improve data analysis, decision making and provide services to customer and be able to answer challenges in the era of innovation and technology sustainable towards the industrial era 5.0. Therefore, the research aims to determine the performance of the banking industry from a comparative perspective before and after the technology and innovation era. The analytical method used is the average difference test of banking industry performance indicators consisting of assets, third party funds (DPK), credit, capital adequacy ratio (CAR), and return on assets (ROA). The research results show that there is an average difference before and after the technology and innovation era in banking performance indicators namely assets, credit CAR and ROA, while there is no average difference in the DPK indicator before and after the technology and innovation era. This means that the era of technology and innovation has an impact on assets, credit, CAR and ROA as performance indicators of the banking industry. However, the era of technology and innovation does not have an impact on DPK, so it is a challenge in itself for sustainable technology and innovation era in welcoming the industrial era 5.0.Keywords: Banking Industry Performance, Assets, DPK, Credit, CAR, ROA, Technology and Innovation Era, Average Difference Test